Economic cost of the lockdown - Pal, Barun Deb; Pohit, Sanjib (2020)
The Indian economy will face an income loss of Rs 1.7 lakh crore per week or a total of Rs 5.1 lakh crore during the three-week-long shutdown called by the Govt.